KEEFEKTIFAN KALIMAT DALAM TEKS BERITA SISWA KELAS VIII SMP PEMBANGUNAN LABORATORIUM UNP - Syafira, Dela; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of this study is to describe the sentences in the student explanation text in terms of four things. First, the effectiveness of sentences in terms of language accuracy, there are 175 (62.94%) errors. Ineffectiveness of the sentence based on elements of syntactic functions (28 errors), missing sentence elements (13 errors), redundant sentence elements (134 errors). Second, the effectiveness of sentences in terms of word accuracy has 18 (06.47%) errors. Ineffectiveness of the sentence lies in the accuracy of the concept (5 errors) and the accuracy of the usage context (13 errors). Third, the effectiveness of sentences in terms of spelling accuracy is 165 (58.63%) errors. The ineffectiveness of the sentence is in the use of capital letters (72 errors), the use of periods (5 errors), the use of commas (40 errors), and writing words (46 errors). Based on these results it can be concluded that the sentences in the news text of class VIII students at SMP Pembangunan Laboratory Laboratory are not effective. This is evidenced from the 278 sentences studied, there were 76 (27.33%) effective sentences and 202 (72.66%) ineffective sentences with 356 errors.Â Kata kunci: Keefektifan Kalimat, Teks Berita